SURGICAL STRATEGY IN BULLET WOUND OF THE THORAX ACCOMPANIED BY SHOCK - D. R. Ivchenko; A. P. Koltovich; A. A. Kukunchikov (Вестник хирургии имени И.И. Грекова)
The article analyzes the experience of treatment of bullet penetrating wounds of the thorax accompanied by shock in 131 armed forces personnel of internal army and officers of the Ministry of Home Affairs of Russia during contra-terrorist operations on the North Caucasus at the period from 2000 to 2011. The postoperative lethality was reduced from 22,7% to 10,8% due to usage of the strategy which was directed to decrease of surgical aggression in 65 patients.